2016
DOI: 10.1158/0008-5472.can-14-1306
|View full text |Cite
|
Sign up to set email alerts
|

STAT3/IRF1 Pathway Activation Sensitizes Cervical Cancer Cells to Chemotherapeutic Drugs

Abstract: Neoadjuvant radio/chemotherapy regimens can markedly improve cervical cancer outcome in a subset of patients, while other patients show poor responses, but may encounter severe adverse effects. Thus, there is a strong need for predictive biomarkers to improve clinical management of cervical cancer patients. STAT3 is considered as a critical antiapoptotic factor in various malignancies. We therefore investigated STAT3 activation during cervical carcinogenesis and its impact on the response of cervical cancer ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 49 publications
7
54
0
Order By: Relevance
“…IRF was identified as a STAT3-inducible proapoptotic factor that mediated chemosensitization of cervical cancer cells by the pretreatment of a pleiotropic cytokine, oncostatin M [52]. In addition, IRF1 expression is associated with response to radio/chemotherapy in cervical cancer patients [52]. Similar to this study, we also found that sequential IFNβ-cisplatin treatment-induced IRF1 expression was responsible for the enhanced anticancer activity of cisplatin.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…IRF was identified as a STAT3-inducible proapoptotic factor that mediated chemosensitization of cervical cancer cells by the pretreatment of a pleiotropic cytokine, oncostatin M [52]. In addition, IRF1 expression is associated with response to radio/chemotherapy in cervical cancer patients [52]. Similar to this study, we also found that sequential IFNβ-cisplatin treatment-induced IRF1 expression was responsible for the enhanced anticancer activity of cisplatin.…”
Section: Discussionsupporting
confidence: 83%
“…IRF1 has been considered a tumor suppressor [47][48][49][50][51]. IRF was identified as a STAT3-inducible proapoptotic factor that mediated chemosensitization of cervical cancer cells by the pretreatment of a pleiotropic cytokine, oncostatin M [52]. In addition, IRF1 expression is associated with response to radio/chemotherapy in cervical cancer patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that stimulation of cervical cancer cells with IL-6 in combination with the soluble IL-6R or OSM can potently activate STAT3 which leads to IRF1 up-regulation (10). Patients with high expression of the STAT3-regulated pro-apoptotic IRF1 in pretreatment cervical cancer biopsy cells showed in fact significantly higher responses to neoadjuvant chemoand chemoradiotherapy (10). In line with this, the in vitro results from this study confirmed that cell death sensitization toward irradiation or chemoradiotherapy is induced by OSM Table I.…”
Section: Discussionmentioning
confidence: 99%
“…We clarified the molecular mechanism responsible for cell death sensitization, which was dependent on the STAT3/IRF1 signaling pathway. This was unexpected because in cervical cancer patients in situ the STAT3 activation is weak or absent (10). This is in contrast to other malignancies, where STAT3 is constitutively active and is a considered anti-apoptotic factor (13)(14)(15).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation